2020
DOI: 10.21203/rs.3.rs-41732/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cost-effectiveness of the Adaptive Implementation of Effective Programs Trial (Adept): Approaches to Adopting Implementation Strategies

Abstract: Background Theory-based methods to support clinician uptake of evidence-based practices (EBPs) are critical to improving mental health outcomes. Costs associated with effective implementation strategies can be substantial, and few have been rigorously evaluated. The purpose of this study is to conduct a cost-effectiveness analysis to identify the most cost-effective approach to deploying implementation strategies to enhance the uptake of Life Goals, a mental health EBP. Methods We used data from a previously… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Guided by the FRAME and other tools [20], mixed methods approaches can be highly useful to elucidate the economic reasons driving the adaptations to improve the generalizability of findings, as well as their economic consequences [21]. Mixed methods can also inform sensitivity analysis that is often a critical component to test the assumptions made in economic evaluation [22], by further identifying and explaining variations in cost at different levels (e.g., provider, practice) and for various stakeholders. For implementation planning purposes, it is useful to understand the dimensions upon which planned adaptations may be warranted and to establish a range in costs associated with planned adaptations that are likely to occur.…”
Section: Mixed Methods Economic Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Guided by the FRAME and other tools [20], mixed methods approaches can be highly useful to elucidate the economic reasons driving the adaptations to improve the generalizability of findings, as well as their economic consequences [21]. Mixed methods can also inform sensitivity analysis that is often a critical component to test the assumptions made in economic evaluation [22], by further identifying and explaining variations in cost at different levels (e.g., provider, practice) and for various stakeholders. For implementation planning purposes, it is useful to understand the dimensions upon which planned adaptations may be warranted and to establish a range in costs associated with planned adaptations that are likely to occur.…”
Section: Mixed Methods Economic Evaluationmentioning
confidence: 99%
“…The trial evaluated implementation strategies of varying intensity, with a lowintensity strategy that includes EBP packaging, training, and technical assistance, followed by a medium-intensity strategy involving facilitation by external experts, and a high-intensity strategy involving internal facilitation with protected time for internal staff to support EBP implementation. Implementation strategies were evaluated for their cost-effectiveness through random assignment in three stages, whereby sites not responding to the implementation strategy in the previous stage were further randomized to receive a supplemental implementation strategy in the subsequent stage [22]. Findings suggested that the most cost-effective implementation support starts with a less intensive, less costly implementation strategy and increases as needed to enhance EBP uptake [22].…”
Section: The Sequential Multiple Assignment Randomized Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design aimed to determine, among clinics that had been non-responsive to REP, the cost-effectiveness of adding external or internal facilitation as supplemental implementation strategies. A cost-effectiveness analysis found that the adaptive strategy that begins with a less intensive, less costly strategy, and increases implementation support based on monitoring the implementation response variable, was the most cost-effective strategy among those tested in the trial [ 45 ]. Resources such as those available at the NIH-funded Methodology Center at Pennsylvania State University [ 46 ] can help implementation researchers design studies that are both statistically rigorous and adaptive in their approach.…”
Section: Implications For Implementation Researchersmentioning
confidence: 99%
“…One approach is a modified cost calculator approach that has been applied in the Costs of Implementing New Strategies (COINS); this approach identifies a range of costs across phases of implementation (e.g., pre-implementation, implementation, and sustainability) tailored to the strategies utilized for a specific implementation effort and focused on the perspective of the organization/provider deciding to adopt the EBI [63][64][65][66]. This is useful in identifying costs related to implementation for several reasons: (1) it aids in determining direct costs of implementation through tallying time spent on activities in each phase of implementation strategy deployment (often the bulk of implementation strategy costs), (2) this practical approach can provide needed guidance and scaffolding for stakeholders and decision-makers to determine implementation costs so organizations could accurately estimate the necessary resources for implementation success, and (3) this approach has been used previously with Enhanced REP in estimating costs as the first step in cost-effectiveness analysis for a community-based clinical trial [67]. Table 4 provides a list of anticipated activities whose costs will be estimated prospectively as part of the pilot trial.…”
Section: Measures Costsmentioning
confidence: 99%